2014
DOI: 10.3390/rs61212789
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of Two Rice Mapping Approaches: Characterizing Strata Mapped by Hypertemporal MODIS and Rice Paddy Identification Using Multitemporal SAR

Abstract: Different rice crop information can be derived from different remote sensing sources to provide information for decision making and policies related to agricultural production and food security. The objective of this study is to generate complementary and comprehensive rice crop information from hypertemporal optical and multitemporal high-resolution SAR imagery. We demonstrate the use of MODIS data for rice-based system characterization and X-band SAR data from TerraSAR-X and CosmoSkyMed for the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 48 publications
(78 reference statements)
2
46
0
Order By: Relevance
“…The free release of Landsat archive data by USGS/EROS provides an unprecedented data source for paddy rice mapping given its ideal spatial resolution and long records dating back to the 1970s. Synthetic Aperture Radar (SAR) is anticipated to play an important role in paddy rice mapping in tropical and subtropical regions given their frequent cloud coverage (Shao et al, 2001) and one study showed its even more promising capability in mapping rice area and transplanting dates (Asilo et al, 2014); however, its acquisition capability is still not as good as optical sensors.…”
Section: Major Characteristics Of Evolution Of Paddy Rice Mapping Metmentioning
confidence: 99%
“…The free release of Landsat archive data by USGS/EROS provides an unprecedented data source for paddy rice mapping given its ideal spatial resolution and long records dating back to the 1970s. Synthetic Aperture Radar (SAR) is anticipated to play an important role in paddy rice mapping in tropical and subtropical regions given their frequent cloud coverage (Shao et al, 2001) and one study showed its even more promising capability in mapping rice area and transplanting dates (Asilo et al, 2014); however, its acquisition capability is still not as good as optical sensors.…”
Section: Major Characteristics Of Evolution Of Paddy Rice Mapping Metmentioning
confidence: 99%
“…The σ° was derived through three processing steps: (a) multi-temporal speckle filtering according to the approach developed by De Grandi et al [59,60,72], to balance differences in reflectivity between images at different times, (b) geocoding and radiometric calibration, using a Digital Elevation Model (SRTM DEM, at 90m equivalent ground resolution) and the radar equation, in which scattering area, antenna gain patterns and range spread loss were considered, and finally (c) normalization on local incidence angle, according to the cosine law. The interferometric coherence γ maps were produced using the complex data of image pairs of consecutive acquisitions [73], with a temporal baseline of 16 days (32 days for the 08 June-10 July 2014 pair).…”
Section: Satellite Data Pre-processingmentioning
confidence: 99%
“…CSK images were pre-processed with MAPscape-RICE software [59] for (i) mosaicking single frames into slant range continuous strips and (ii) co-registration of images using orbital information and automatic spatial matching based on cross-correlation.…”
Section: Satellite Data Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…span), which are indicators of the presence of flooded conditions, rice biomass accumulation and rapid rice growth after flooding, respectively. As we specified above, TSD are computed over different time horizons to be diagnostic indicators of rice growing and/ or agronomic practices for the discrimination between rice and other crops (Asilo et al, 2014;Fontanelli et al, 2014;Villa et al, 2015) (Table 1). Both time horizons and the threshold values can be adapted and refined to different crop and environmental conditions.…”
Section: Early Rice Mapping: Temporal Spectral Descriptors Approachmentioning
confidence: 99%